The Form of a Promise of the Gift (Gift Promise) of Movables - Miščević, Nikolina B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Summary: This paper will discuss the form of a gift when the subject of the agreement is a the transfer of ownership of movables. More precisely, the subject matter of this paper is the form of a gift promise, i.e. gift agreement which is concluded without the simultaneous handover of the thing. As the gift agreement is not regulated by the applicable regulation, the rules of the pre-war law apply to it. However, when it comes to the form of the gift agreement, in the domestic law occur, since the Serbian Civil Code up until this day, different legislative solutions and proposals for its regulation. Therefore, it is not entirely quite easy to answer the question of what rules should apply to questions concerning the form of a gift promise when it comes to movables. Also, other issues regarding the form of the gift promise are being disputed in domestic theory. This paper presents legislative solutions and proposals for solutions regulating the form of a gift promise since the Serbian Civil Code up until this day, as well as solutions from comparative law that have served as a model for regulating it. In addition, various authors' perceptions of the form of the gift promise and the consequences of lack of the obligatory form are presented. Lastly, the paper proposes how the form of the gift promise should be regulated in order to eliminate existing ambiguities. Keywords: form of the agreement, gift agreement, gift promise, form of a gift promise, consequences of the lack of the form of a gift promise.